2016
DOI: 10.1530/eje-16-0289
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Endogenous subclinical hypercortisolism and bone: a clinical review

Abstract: In recent years, the condition of subclinical hypercortisolism (SH) has become a topic of growing interest. This is due to the fact that SH prevalence is not negligible (0.8-2% in the general population) and that, although asymptomatic, this subtle cortisol excess is not harmless, being associated with an increased risk of complications, in particular of osteoporosis and fragility fractures. As specific symptoms of hypercortisolism are absent in SH, the SH diagnosis relies only on biochemical tests and it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 134 publications
1
56
1
1
Order By: Relevance
“…Regarding bone metabolism impairment in SCS, the risk of developing osteoporosis is enhanced by the overproduction of cortisol in SCS [37,38]. On the other The numbers of patients who remained after the exclusion of 2 patients who had bilateral tumors and who missed the maximum tumor diameter c…”
Section: Discussionmentioning
confidence: 99%
“…Regarding bone metabolism impairment in SCS, the risk of developing osteoporosis is enhanced by the overproduction of cortisol in SCS [37,38]. On the other The numbers of patients who remained after the exclusion of 2 patients who had bilateral tumors and who missed the maximum tumor diameter c…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of studies demonstrating that ACS patients present with higher metabolic disorders frequency caused by excess cortisol . Regarding NFAI, its definition includes absence of hypercortisolism as well as any other relevant hormonal activity and the guidelines do not indicate extra care.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of studies demonstrating that ACS patients present with higher metabolic disorders frequency caused by excess cortisol. 5,20,[33][34][35][36][37] Regarding NFAI, its definition includes absence of and their levels usually increase with obesity. 39,40 In agreement, our study demonstrated that even both groups having comparable BMI the signs of insulin resistance were significantly higher in the NFAI group, which might point to a probable difference in the quality of the adipose tissue of these patients or higher circulating levels of me-…”
Section: Discussionmentioning
confidence: 99%
“…The condition of mild autonomous cortisol secretion (ACS) is characterized by an increased cortisol secretion in the absence of the classical signs of overt cortisol excess (1,2), and it is found in up to 20% of patients bearing an incidentally discovered adrenal mass (adrenal incidentaloma, AI) (3,4). In adults, mild ACS has a 0.2-2.0% prevalence and it seems to be associated with an increased risk of fragility fractures, dyslipidemia (DL), type 2 diabetes (T2DM), hypertension (AH), cardiovascular events (CVE) and mortality (5,6,7,8,9,10,11). However, since the improvement of the metabolic complications after the recovery from mild ACS has been not consistently reported (12,13), no widely accepted guidelines are available on how to define mild ACS and to address the treatment in AI patients with subtle hypercortisolism (1,15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%